Genetic Relatedness Between Batur, Merino and Local Sheep Based on Random Amplyfied Polymorphism DNA Marker - Prayitno, Prayitno; Hartatik, T; Pratiwi, R; Artama, WT (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
RAPD analysis to determine the diversity, status and genetic close relatioship Batur with Merino, Garut, Thin Tail and Fat Tail sheep genomic DNA was used in 27 Batur, 15 Merino, 17 Garut, 15 Thin Tails and Fat Tails animals. The process of RAPD-PCR used five primers of 10 nucleotides. PCR results were electrophoresed with 2% agarose gel. Identified similarities and differences between individual RAPD bands one and cross-sample of the population, genetic distance and closeness of genetic relationship. The process 89 sample sheep RAPD-PCR generated of 4189 band from 100 to 1500 bp which consisted of 91 type. Batur sheep samples produced bands at most (1666 tape) and the lowest Fat Tails (493 bands). The number monomorfism of bands most of the Batur (891 bands) and the lowest Garut (170 bands), but the polymorphism bands highest of the Batur (775 bands) and the lowest Fat Tails (262 bands). Between individuals within populations have similar genetic Merino highest and the lowest Thin Tail. Cross-population genetic similarity is highest individuals in the population Batur and Merino, while the lowest Merino and Thin Tail. The closest genetic distance was Batur with Merino population and the most apart distant Merino with Thin Tail or Merino and Fat Tails. Batur sheep population has the closest genetic relationship with the Merino and the most apart distant is with Fat Tail. (Animal Production 13(1):30-38 (2011)Key Words: RAPD, genetic markers, genetic similarity, sheep